Trends of under-five mortality and associated risk factors in Zambia: a multi survey analysis between 2007 and 2018 - Amanuel Kidane Andegiorgish; Henok G. Woldu; Mohamed Elhoumed; Zhonghai Zhu; Lingxia Zeng (BMC, 2022)
Abstract Background Mortality at a young age is key to public health measures. This study aims to describe the burden, trend, and associated factors of under-five mortality rate (U5MR) in Zambia from 2007-to-2018. Method A sample of 29,274 children under-five were analyzed from the Zambia demographic and health survey (ZDHS). Univariate and bivariate analysis were used to identify factors influencing U5M. Result Pooled prevalence of U5MR in Zambia was 84.4/ 1000 live-births. Over 15 years, U5M has declined by 49% (from 118.7 to 60.5/1000 live-births). Compared to children of teenage (≤19 years) mothers the likelihood of U5M was lower by 24 to 37% among children of 20 to 34 years old mothers. The likelihood of U5M was lower by 23% (AOR, 0.77 95%CI, 0.58-1.04) for poorest, 27% (AOR, 0.73 95%CI, 0.55-0.98) for poorer, and 19% (AOR, 0.81 95%CI, 0.62-1.07) for middle as compared to the richest households. The likelihood of U5M was 21% (AOR, 0.79 95%CI, 0.67-0.93) lower among rural residents. Multiple-born children died 2.54 times (95%CI, 1.95-3.98) higher than the single-born. Male children (AOR, 1.28, 95% CI, 1.23-1.46), smaller than average birth size (AOR, 1.78; 95% CI, 1.52-2.09), and no ANC visit (AOR, 3.17, 95% CI, 2.74-3.67) were associated with U5M. The likelihoods of U5M were significantly higher in the Eastern, Luapula, and Muchinga regions than in the Central. Conclusion This study revealed that Zambia has made a gain on child survival. Further efforts targeting mothers, children, and provinces are needed to scale up the decline and achieve the SDG3.